JURIDICAL REVIEW OF MEDICAL SERVICES AT LABUANG BAJI REGIONAL GENERAL HOSPITAL, MAKASSAR CITY ACCORDING TO LAW NO. 36 YEAR 2009 CONCERNING HEALTH - Siti Amimah (Fox Justi : Jurnal Ilmu Hukum, 2021)
This study aims to determine: (1) how is the legal relationship between doctors and patients in the action of medical services at the Labuang Baji General Hospital Makassar. (2) Is every doctor responsible for the patient in an effort to provide medical services at the hospital? (3) What are the factors that influence the implementation of medical services at the Labuang Baji Regional General Hospital, Makassar City. Based on the results of this study indicate that 1) The legal relationship that occurs between doctors and patients in the action of medical services at the Labuang Baji Makssar Regional General Hospital is when the patient states his complaint and is then responded to by the doctor and when the patient is examined by the doctor, where the doctor has expressed his willingness which is expressed verbally or implicitly in showing an attitude or action that concludes the doctor's willingness. 2) a doctor is always responsible for every action given to his patient. 3) The factors that influence the implementation of medical services in hospitals are: the gap between the expectations of the patient or the patient's family towards the medical profession